2017
DOI: 10.1080/23802359.2017.1357437
|View full text |Cite
|
Sign up to set email alerts
|

The complete mitochondrial genome of Geochelone sulcata

Abstract: The complete mitochondrial genome of Geochelone sulcata was determined using PCR, Long-PCR with length of 16,692 bp. The genome organization, gene order, and base composition was similar to typical vertebrate. Gene content included 13 protein-coding genes, 22 tRNA genes, two rRNA genes, and one control region. Otherwise, the lack of C, as same as in the other species of Testudinidae, was detected in arms of tRNA Lys gene in G. sulcata. In addition, an extra nucleotide A was discovered in ND3 gene in G. sulcata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The complete mitochondrial genomic analysis of C. sulcata revealed that the gene content included 13 proteincoding genes, 22 tRNA genes, two rRNA genes, and one control region (Shi et al 2017). Otherwise, the lack of cytosine, as in other species of Testudinidae, was detected in arms of the tRNALys gene.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…The complete mitochondrial genomic analysis of C. sulcata revealed that the gene content included 13 proteincoding genes, 22 tRNA genes, two rRNA genes, and one control region (Shi et al 2017). Otherwise, the lack of cytosine, as in other species of Testudinidae, was detected in arms of the tRNALys gene.…”
mentioning
confidence: 95%
“…Otherwise, the lack of cytosine, as in other species of Testudinidae, was detected in arms of the tRNALys gene. In addition, an extra nucleotide adenine was discovered in the ND3 gene (Shi et al 2017).…”
mentioning
confidence: 99%